Rapid, remote and responsive research during COVID-19 - Jane Richardson; Barry Godfrey; Sandra Walklate (Methodological Innovations, 2021)
In March 2020, the UK Research and Innovation announced an emergency call for research to inform policy and practice responses to the COVID-19 pandemic. This call implicitly and explicitly required researchers to work rapidly, remotely and responsively. In this article, we briefly review how rapid response methods developed in health research can be used in other social science fields. After outlining the literature in this area, we use the early stages of our applied research into criminal justice responses to domestic abuse during COVID-19 as a case study to illustrate some of the practical challenges we faced in responding to this rapid funding call. We review our use of and experience with remote research methods and describe how we used and adapted these methods in our research, from data gathering through to transcription and analysis. We reflect on our experiences to date of what it means to be responsive in fast-changing research situations. Finally, we make some practical recommendations for conducting applied research in a ‘nimble’ way to meet the demands of working rapidly, remotely, responsively and, most importantly, responsibly.